Huangqi Guizhi Wuwu decoction promotes M2 microglia polarization and synaptic plasticity via Sirt1/NF-κB/NLRP3 pathway in MCAO rats - Ou, Zhijie; Zhao, Min; Xu, Ying; Wu, Yan; Qin, Lina; Fang, Li; Xu, Hong; Chen, Juping (Aging (Albany, NY.), 2023)
Huangqi Guizhi Wuwu decoction (HGWD) has been demonstrated to ameliorate cerebral ischemia-reperfusion injury in clinical application. Nevertheless, the exact mechanisms of HGWD have not been conclusively elucidated. This study aimed to investigate the potential role and mechanism of HGWD on neurological deficits in a rat model of middle cerebral artery occlusion (MCAO). Our results showed that HGWD significantly alleviated neurological deficits in MCAO rats, evidenced by high mNSS score, reduced cerebral infarction area, and improved brain pathological injury. Besides, HGWD reduced the levels of TNF-α, IL-1β, IL-6, SOD, MDA and GSH in the brain tissue. Further study suggested that HGWD promoted microglia polarization towards M2 by inhibiting M1 activation (Iba1+/CD16+, iNOS) and enhancing M2 activation (Iba1+/CD206+, Arg-1). Additionally, HGWD increased dendritic spine density and enhanced levels of synapse marker proteins (PSD95, Synapsin I). HGWD also up-regulated Sirt1 expression while inhibited p-NF-κB, NLRP3, ASC, and cleaved caspase-1 level in the hippocampus of MCAO rats. Sirt1 specific inhibitor EX527 notably weakened the neuroprotective efficacy of HGWD against cerebral ischemia, and significantly abolished its modulation on microglia polarization and synaptic plasticity in vivo. Collectively, our findings suggested that HGWD ameliorated neuronal injury in ischemic stroke by modulating M2 microglia polarization and synaptic plasticity, at least partially, via regulating Sirt1/NF-κB/NLRP3 pathway, further supporting HGWD as a potential therapy for neuroprotection after ischemic stroke.Huangqi Guizhi Wuwu decoction (HGWD) has been demonstrated to ameliorate cerebral ischemia-reperfusion injury in clinical application. Nevertheless, the exact mechanisms of HGWD have not been conclusively elucidated. This study aimed to investigate the potential role and mechanism of HGWD on neurological deficits in a rat model of middle cerebral artery occlusion (MCAO). Our results showed that HGWD significantly alleviated neurological deficits in MCAO rats, evidenced by high mNSS score, reduced cerebral infarction area, and improved brain pathological injury. Besides, HGWD reduced the levels of TNF-α, IL-1β, IL-6, SOD, MDA and GSH in the brain tissue. Further study suggested that HGWD promoted microglia polarization towards M2 by inhibiting M1 activation (Iba1+/CD16+, iNOS) and enhancing M2 activation (Iba1+/CD206+, Arg-1). Additionally, HGWD increased dendritic spine density and enhanced levels of synapse marker proteins (PSD95, Synapsin I). HGWD also up-regulated Sirt1 expression while inhibited p-NF-κB, NLRP3, ASC, and cleaved caspase-1 level in the hippocampus of MCAO rats. Sirt1 specific inhibitor EX527 notably weakened the neuroprotective efficacy of HGWD against cerebral ischemia, and significantly abolished its modulation on microglia polarization and synaptic plasticity in vivo. Collectively, our findings suggested that HGWD ameliorated neuronal injury in ischemic stroke by modulating M2 microglia polarization and synaptic plasticity, at least partially, via regulating Sirt1/NF-κB/NLRP3 pathway, further supporting HGWD as a potential therapy for neuroprotection after ischemic stroke.